PENGARUH HARGA, DISTRIBUSI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN OBAT BATUK KOMIX PADA PT ENSEVAL PUTERA MEGATRADING, TBK - Purnamasari, Dian (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2023)
The purpose of this study to determine how the price, distribution and promotion influence on purchase decisions. This research is a simple random sampling, the number of object is 50 sample. The research method used in this research is deskriptive quantitative approaches supported qualitative method.The sampling in this study using sampling technique Probability Sampling. The software used to process and analyze the data of this study was SPSS version 23.0.Based on the result of t test analysis, it is known that tcount<ttable is 0.014<2.012with significance 0.989,so decision taken is Ho accepted and Ha rejected. These results indicate that the price partially does not give significant effect on Purchase Decisionsat PT Enseval Putera Megatrading, Tbk. Based on the result of t test analysis, it is known that tcount> ttable is 4.792 > 2.012with significance 0.000, so the decision taken is Ho rejected and Ha accepted. These results indicate that partially distribution has significant effect on Purchase Decisionsat PT Enseval Putera Megatrading, Tbk. Based on the result of ttest analysis, it is known that tcount> ttable is 1.143 < 2.012with significance 0.259,so decision taken is Ho accepted and Ha rejected. These results indicate that the promotion partially does not give significant effect on Purchase Decisionsat PT Enseval Putera Megatrading, Tbk. Based on the result of F test analysis, it is known that Fcount> Ftable 13.658>2.574 with significance value 0.001, so that decision taken is Ho refused and Ha accepted. These results indicate that all independent variables (Price, Distribution and Promotion) influence simultaneously or together to give to the performance of Purchase Decisionsat PT Enseval Putera Megatrading, Tbk.